Content Mastery Services using Small Group Discussion Learning Model to Improve Students' Interpersonal Communication Abilities - Kurniawan, Rizki; Neviyarni (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Poor interpersonal communication skills will hinder students in building and maintaining harmonious relationships. Effective communication if utilized properly has the potential to prevent and resolve problems or conflicts between individuals, groups, tribes, nations, and races. Efforts to improve students' interpersonal communication skills are carried out by providing material mastery services through small group discussion learning models. This study aims to evaluate the effectiveness of material mastery services through small group discussion learning models by comparing achievements before and after treatment. This study uses quantitative methodology. This study is a quasi-experimental study with a non-equivalent control group design. The study population was junior high school students, with samples taken using the Purposive Sampling technique, namely two classes classified as moderate interpersonal contact, both of which are equivalent. This study uses the Likert Scale paradigm for data collection, which is then analyzed using the Wilcoxon Signed Ranks Test and the Mann-Whitney U Test, facilitated by SPSS version 26. This study concludes that topic mastery services using the small group discussion model effectively improve students' interpersonal communication skills. The gap in interpersonal communication skills between students in the experimental group, who received content mastery services through a small group discussion model, and those in the control group, who were only given structured content mastery services, was 0.000, indicating a probability below 0.05 (0.000 < 0.05).